2011
DOI: 10.1177/1468798411409297
|View full text |Cite
|
Sign up to set email alerts
|

Using popular culture print to increase emergent literacy skills in one high-poverty urban school district

Abstract: This study has focused on using the text associated with popular culture print to teach early literacy skills to pre-kindergarten students. This study examined whether explicitly using popular culture print to teach alphabet knowledge and print concepts increased the achievement of these skills. Data revealed an increase in the mean rank of the experimental group on the post-test of alphabet knowledge. Also, a statistically significant difference appeared to exist between the control and experimental groups' m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
42
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(50 citation statements)
references
References 26 publications
6
42
0
2
Order By: Relevance
“…Therefore, environmental print may be a suitable resource for fostering letter and word knowledge because of its salient visual properties (e.g., size of letters and words) and ubiquitous, meaningful, and functional nature. Moreover, a number of intervention studies have shown that scaffolding preschooler's interactions with environmental print fosters emergent literacy skills such as letter knowledge, print concepts, and emergent writing (e.g., Neumann, Hood, & Ford, ; Prior, ; Vera, ). Thus, further eye tracker research using a pre–post test design will help determine whether providing environmental print strategies (e.g., by pointing to the environmental print letter, saying its name and sound, and tracing the letter with a finger; Neumann et al., ) does in fact increase children's visual attention to and knowledge of letters and words.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, environmental print may be a suitable resource for fostering letter and word knowledge because of its salient visual properties (e.g., size of letters and words) and ubiquitous, meaningful, and functional nature. Moreover, a number of intervention studies have shown that scaffolding preschooler's interactions with environmental print fosters emergent literacy skills such as letter knowledge, print concepts, and emergent writing (e.g., Neumann, Hood, & Ford, ; Prior, ; Vera, ). Thus, further eye tracker research using a pre–post test design will help determine whether providing environmental print strategies (e.g., by pointing to the environmental print letter, saying its name and sound, and tracing the letter with a finger; Neumann et al., ) does in fact increase children's visual attention to and knowledge of letters and words.…”
Section: Discussionmentioning
confidence: 99%
“…These skills are important precursors for future reading development (Australian Government, 2005;Snow, Burns, & Griffin, 1998). In addition to shared storybook reading, a potentially important way that young children come to experience print is through shared interactions with environmental print (Enz, Prior, Gerard, & Han, 2008;Neumann, Hood, Ford, & Neumann, 2012;Vera, 2011). Environmental print is defined as surrounding noncontinuous print that fulfills real-life functions and that appears in a variety of fonts, shapes, and sizes and generally in capital letters (e.g., Horner, 2005;Vukelich, Christie, & Enz, 2008).…”
Section: Mother-child Referencing Of Environmental Print and Its Relamentioning
confidence: 98%
“…Vera (2007) examined the effects of a nine-week environmental print intervention (N ¼ 56) within a pre-kindergarten literacy curriculum. Popular culture environmental print logos familiar to the children (e.g.…”
Section: Environmental Print Use By Parentsmentioning
confidence: 99%